A Framework for Crafting Clinical Practice Guidelines that are Relevant to the Care and Management of People with Multimorbidity - Uhlig, Katrin (Springer US, 2014)
Many patients of all ages have multiple conditions, yet clinicians often lack explicit guidance on how to approach clinical decision-making for such people. Most recommendations from clinical practice guidelines (CPGs) focus on the management of single diseases, and may be harmful or impractical for patients with multimorbidity. A major barrier to the development of guidance for people with multimorbidity stems from the fact that the evidence underlying CPGs derives from studies predominantly focused on the management of a single disease. In this paper, the investigators from the Improving Guidelines for Multimorbid Patients Study Group present consensus-based recommendations for guideline developers to make guidelines more useful for the care of people with multimorbidity. In an iterative process informed by review of key literature and experience, we drafted a list of issues and possible approaches for addressing important coexisting conditions in each step of the guideline development process, with a focus on considering relevant interactions between the conditions, their treatments and their outcomes. The recommended approaches address consideration of coexisting conditions at all major steps in CPG development, from nominating and scoping the topic, commissioning the work group, refining key questions, ranking importance of outcomes, conducting systematic reviews, assessing quality of evidence and applicability, summarizing benefits and harms, to formulating recommendations and grading their strength. The list of issues and recommendations was reviewed and refined iteratively by stakeholders. This framework acknowledges the challenges faced by CPG developers who must make complex judgments in the absence of high-quality or direct evidence. These recommendations require validation through implementation, evaluation and refinement.